The role of the foreign assets in the economy of Ukraine at the turn of the XXth century - Lantukh, I. (Економічний вісник Донбасу, 2016)
The article proves the effectiveness of foreign assets at traction to the domestic investment enterprise at the end of the 19th c. The author determines attractiveness of the domestic business, which was being modernized during the factory-and-plant industrialization and required strong financial donors, for foreign direct investments. Attention is paid to the monetary reform of 1895-1897, which facilitated the process of foreign capital penetration to the domestic market. Also, a parallel is drawn with the modern foreign direct investments to Ukraine and their vectors are analysed.